2020
DOI: 10.1038/s41467-020-18876-w
|View full text |Cite
|
Sign up to set email alerts
|

Significant increase of global anomalous moisture uptake feeding landfalling Atmospheric Rivers

Abstract: One of the most robust signals of climate change is the relentless rise in global mean surface temperature, which is linked closely with the water-holding capacity of the atmosphere. A more humid atmosphere will lead to enhanced moisture transport due to, among other factors, an intensification of atmospheric rivers (ARs) activity, which are an important mechanism of moisture advection from subtropical to extra-tropical regions. Here we show an enhanced evapotranspiration rates in association with landfalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 58 publications
2
50
0
2
Order By: Relevance
“…Although we revealed how was the moisture accumulated and transported to Japan, this study was mainly based on one major event during the 20HR; multi-casts and longer simulations could reduce the potential uncertainties. On the other hand, recent studies have revealed that AR activities and related extreme precipitation events were enhanced during the past decades due to the warming climate (e.g., Algarra et al, 2020;Payne et al, 2020 and references therein). Therefore, our study also suggests the potential impacts of recent increasing SSTs over the subtropical WP (e.g., Bulgin et al, 2020) on the recorded heavy rainfall in Japan by enhancing the local evaporation and convection.…”
Section: Discussionmentioning
confidence: 99%
“…Although we revealed how was the moisture accumulated and transported to Japan, this study was mainly based on one major event during the 20HR; multi-casts and longer simulations could reduce the potential uncertainties. On the other hand, recent studies have revealed that AR activities and related extreme precipitation events were enhanced during the past decades due to the warming climate (e.g., Algarra et al, 2020;Payne et al, 2020 and references therein). Therefore, our study also suggests the potential impacts of recent increasing SSTs over the subtropical WP (e.g., Bulgin et al, 2020) on the recorded heavy rainfall in Japan by enhancing the local evaporation and convection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to Dettinger et al (2015), exports of tropical moisture (TMEs) occur in zones of intense vapor transport out of the tropics. These TMEs can provide important amounts of vapor for ARs, although most ARs additionally incorporate moisture from midlatitude sources and convergences of vapor along their paths (Algarra et al, 2020; Ramos et al, 2016a).…”
Section: Ars a Phenomenological Definitionmentioning
confidence: 99%
“…With this definition in mind, the major areas affected by ARs generally correspond to the western regions of the continents (Algarra et al, 2020), with most of the impacts of extreme precipitation and floods in the western United States (e.g., Ralph et al, 2013; Corringham et al, 2019; Albano et al, 2020), western Europe (e.g., Eiras‐Barca et al, 2016; Ramos et al, 2015), western South America (e.g. Valenzuela & Garreaud, 2019; Viale et al, 2018), western South Africa (Blamey et al, 2018; Ramos et al, 2019), and the polar regions (e.g., Gorodetskaya et al, 2020; Nash et al, 2018).…”
Section: Ars a Phenomenological Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistically significant increases in the IVT magnitude at landfall are also observed for South Island ARs during autumn and spring (equivalent to a mean increase of 100 − 160 kgm −1 s −1 , p<0.15). In a global study of anomalous moisture uptake associated with ARs, Algarra et al, (2020) found a statistically significant increase in evapotranspiration rates associated with New Zealand landfalling ARs between 1980-2017. Thus, anomalous uptake of moisture likely contributed to the observed AR frequency trend, and intensification of ARs.…”
Section: Interaction Between Climate Oscillationsmentioning
confidence: 99%